Ewing‐like sarcoma: An emerging family of round cell sarcomas. Issue 6 (26th September 2018) - Renzi, Samuele; Anderson, Nathaniel D.; Light, Nicholas; Gupta, Abha
Abstract: Ewing‐like sarcomas are an emerging subgroup of small round blue cell sarcomas that share various degrees of morphological, immunohistochemical, molecular, and clinical similarity with Ewing sarcoma. Despite these similarities, Ewing‐like sarcomas lack the pathognomonic molecular hallmark of Ewing sarcoma: A translocation between a gene of the RNA‐binding TET family ( EWSR1 or FUS ) with a gene of the ETS‐transcription family ( FLI1, ERG, ETV1, ETV4, or FEV ). Recently, increased use of modern molecular methods based on next‐generation sequencing have enabled the identification of distinct subgroups within this previously uncharacterized group of Ewing‐like sarcomas based on the discovery of novel molecular driving events. The focus of this review is to provide an update on the main subcategories of Ewing‐like sarcomas discovered to date: CIC ‐rearranged sarcomas, BCOR ‐rearranged sarcomas, sarcomas with a rearrangement between EWSR1 and a non‐ETS family gene, and the substantial fraction of tumors which remain uncharacterized by molecular methods. There is increasing evidence that these tumors represent stand‐alone entities with unique characteristics rather than simply a subgroup of Ewing sarcoma; thus, the question of the best therapeutic approach for these often aggressive sarcomas remains of primary importance. Ultimately, large collaborative efforts will be necessary to better determine the characteristics of this rare, heterogeneous family of tumors. Abstract : Ewing‐like sarcomas are an emerging subtype of round blue cell tumor. Recent molecular analysis have enabled the discovery of multiple subgroups with potential implications on diagnosis, prognosis, and treatment of these rare neoplastic diseases.